2017
DOI: 10.1126/scitranslmed.aan0820
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical modeling highlights the therapeutic potential of hematopoietic stem cell gene editing for correction of SCID-X1

Abstract: Targeted genome editing in hematopoietic stem/progenitor cells (HSPCs) is an attractive strategy for treating immunohematological diseases. However, the limited efficiency of homology-directed editing in primitive HSPCs constrains the yield of corrected cells and might affect the feasibility and safety of clinical translation. These concerns need to be addressed in stringent preclinical models and overcome by developing more efficient editing methods. We generated a humanized X-linked severe combined immunodef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
225
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(239 citation statements)
references
References 45 publications
13
225
1
Order By: Relevance
“…Reductions in gene editing rates from in vitro to in vivo studies have been reported by other groups using similar gene editing reagents in hematopoietic stem cells. (Genovese et al , 2014; Hoban et al , 2015; De Ravin et al , 2016; Schiroli et al , 2017) Selection methods using reporter genes may be able to overcome the problem(Dever et al , 2016), but this method has not been shown to be scalable to human trials of gene editing due a significant loss of HSC numbers. However, despite the reduced editing rates in vivo, it is likely that in XHIM a proportionally small number of gene-corrected T cells will be sufficient to allow enough class-switching to significantly ameliorate or cure the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in gene editing rates from in vitro to in vivo studies have been reported by other groups using similar gene editing reagents in hematopoietic stem cells. (Genovese et al , 2014; Hoban et al , 2015; De Ravin et al , 2016; Schiroli et al , 2017) Selection methods using reporter genes may be able to overcome the problem(Dever et al , 2016), but this method has not been shown to be scalable to human trials of gene editing due a significant loss of HSC numbers. However, despite the reduced editing rates in vivo, it is likely that in XHIM a proportionally small number of gene-corrected T cells will be sufficient to allow enough class-switching to significantly ameliorate or cure the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, although the cells that originated the malignancy were corrected (transduced) for the γc‐deficiency, the leukemic cells had a transcription pattern identical to normal wild‐type, nontransduced T lymphocytes, suggestive that genotoxicity did not occur . The work from Naldini's laboratory elegantly explored several additional aspects that must be taken into account when attempting to correct the γ c genetic defect by gene therapy . This group generated their own mouse model of SCID‐X1, mimicking a null mutation from patients.…”
Section: Relevance Of Bone Marrow Reconstitution For Correction Of Scmentioning
confidence: 99%
“…Today, this is most often done by 6 of 12 EMBO Molecular Medicine 11: e9958 | 2019 ª 2019 The Author electroporating purified nuclease ribonucleoprotein complexes (i.e., Cas nucleases preassembled with single guide RNA) or nucleaseencoding mRNAs (for the other platforms), followed, when required, by the delivery of the repair template through a viral vector, such as adeno-associated virus-derived (AAV6) or integrase-defective LV (IDLV) (Genovese et al, 2014;Wang et al, 2015;Dever et al, 2016;De Ravin et al, 2016aSchiroli et al, 2017). Today, this is most often done by 6 of 12 EMBO Molecular Medicine 11: e9958 | 2019 ª 2019 The Author electroporating purified nuclease ribonucleoprotein complexes (i.e., Cas nucleases preassembled with single guide RNA) or nucleaseencoding mRNAs (for the other platforms), followed, when required, by the delivery of the repair template through a viral vector, such as adeno-associated virus-derived (AAV6) or integrase-defective LV (IDLV) (Genovese et al, 2014;Wang et al, 2015;Dever et al, 2016;De Ravin et al, 2016aSchiroli et al, 2017).…”
Section: Precision Genetic Engineering: Targeted Gene Editingmentioning
confidence: 99%
“…Today, this is most often done by 6 of 12 EMBO Molecular Medicine 11: e9958 | 2019 ª 2019 The Author electroporating purified nuclease ribonucleoprotein complexes (i.e., Cas nucleases preassembled with single guide RNA) or nucleaseencoding mRNAs (for the other platforms), followed, when required, by the delivery of the repair template through a viral vector, such as adeno-associated virus-derived (AAV6) or integrase-defective LV (IDLV) (Genovese et al, 2014;Wang et al, 2015;Dever et al, 2016;De Ravin et al, 2016aSchiroli et al, 2017). We and others could overcome at least in part these barriers by extending culture in conditions that drive even the most primitive cells into replication while preserving their engraftment capacity and by tailoring the gene editing machinery to avoid triggering innate immune cellular responses (Genovese et al, 2014;Wang et al, 2015;De Ravin et al, 2016aDever et al, 2016;Schiroli et al, 2017). All these approaches have the advantage to achieve a high but transient spike of nuclease expression in the cultured cells, thus limiting its activity to a small window of time and, consequently, alleviating toxicity and off-target activity.…”
Section: Precision Genetic Engineering: Targeted Gene Editingmentioning
confidence: 99%
See 1 more Smart Citation